2015
DOI: 10.1108/ajim-04-2015-0056
|View full text |Cite
|
Sign up to set email alerts
|

Serendipity in legal information seeking behavior

Abstract: Purpose – The purpose of this paper is to investigate the role of serendipity in legal information seeking behavior of family law advocates, whom act in a challenging information environment that lacks published court rulings. Design/methodology/approach – A quantitative research using a web-based structured questionnaire, among Israeli family law advocates. Single stage systematic sampling, with random starting point and no recurring pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 45 publications
2
14
0
1
Order By: Relevance
“…Chowdhury 15 , et al also supported this with viewpoints that uncertainty is not limited to a cognitive state of the gap in knowledge. However, it may be correlated with difficulties relating to information seeking and retrieval of legal information, lack of awareness and unfamiliarity with sources of information.…”
Section: Literature Reviewmentioning
confidence: 78%
See 1 more Smart Citation
“…Chowdhury 15 , et al also supported this with viewpoints that uncertainty is not limited to a cognitive state of the gap in knowledge. However, it may be correlated with difficulties relating to information seeking and retrieval of legal information, lack of awareness and unfamiliarity with sources of information.…”
Section: Literature Reviewmentioning
confidence: 78%
“…Author of a research study opined that primary legal information should be available free to all, and this can be Further, a question was asked to describe their preferences for search operators. It is found that majority of academic lawyers opted for Boolean operator (122), followed by range operator (67), concept operator (55), proximity operator (43), fuzzy search operator (15), string wild card operator (14), wild card (14), query level (13), selectable truncation (11), not same operator (8), same operator (7). The preferences of practicing lawyers were different and majority of them asked for Boolean operator (83), followed by concept operator (37), range operator (35), proximity operator (26), query level (13), string wild card (10), wild card (7), selectable truncation (7), same operator (7), fuzzy search operator (7).…”
Section: Hindrances In Accessing Open Access Legal Resourcesmentioning
confidence: 99%
“…Lawyers, much like other occupations, may encounter knowledge gaps and a need for professional information when practising law (Solomon and Bronstein, 2015;Wilkinson, 2001;Van Opijnen and Santos, 2017). Cohen (1969) established that when dealing with a new issue, lawyers may operate in several ways: inspect the files and notes of previous cases they have dealt with that are relevant to the issue in question, seek the advice of their peers, transfer the case to another lawyer (for example, due to the case requiring different legal expertise), perform independent legal research using various sources of information, or, in the case of a lawyer in a large firm, delegate the required legal research to a junior associate.…”
Section: Prior Work On the Information Practices Of Lawyersmentioning
confidence: 99%
“…Cohen (1969) established that when dealing with a new issue, lawyers may operate in several ways: inspect the files and notes of previous cases they have dealt with that are relevant to the issue in question, seek the advice of their peers, transfer the case to another lawyer (for example, due to the case requiring different legal expertise), perform independent legal research using various sources of information, or, in the case of a lawyer in a large firm, delegate the required legal research to a junior associate. Following Cohen's study, the research on this topic developed, one can list today studies on the information-seeking behavior of a wide range of legal practitioners, including judges (Mansour and Ghuloum, 2016), practising lawyers (Otike, 1999;Wilkinson, 2001;Solomon and Bronstein, 2015;Fagbemi, 2017;Jamshed, 2020), legal academics and teaching faculty (Khan and Bhatti, 2012;Makri et al, 2008), as well as law students (Kerins et al, 2004;Makri et al, 2006;Kadli and Hanchinal, 2015).…”
Section: Prior Work On the Information Practices Of Lawyersmentioning
confidence: 99%
“…Essas experiências de descoberta acidental de informação remetem ao conceito de serendipidade (serendipity), cuja temática ganhou importância na Ciência da Informação nos últimos anos (SOLOMON;BRONSTEIN, 2016), porém no Brasil é abordada ainda de maneira incipiente no cenário deste campo científico.…”
Section: Atualmente Podem Ser Citados O Comportamento Informacional unclassified